Technology-assisted Qur'an Hadith Learning to Improve Student Achievement - Taufik, Herman; Putra, Sudarmadi; Badruzzaman, Badruzzaman; Haluti, Farid; Hasim, Hasim (World Psychology, 2024)
Technology at this time cannot be separated from human life. In the field of education, technology can facilitate the teaching and learning process, one of which is in the subject of Al-Qur'an Hadith. The purpose of this study was to determine the extent to which the improvement of student achievement in learning Al-Qur'an Hadith with the help of technology. This research method is a quantitative approach using a survey model and in-depth interviews. The survey used in the study was online-based in one of the schools in Payakumbuh. The results of this research show that with the help of technology students' understanding in learning Al-Qur'an Hadith has increased. The conclusion of this study is that technology is very helpful in the learning process of Al-Qur'an Hadith, thus increasing students' enthusiasm for learning and improving students' academic achievement. The limitation in this study is that researchers only conducted research on how to improve student achievement in learning Al-Qur'an Hadith with the help of technology, therefore researchers hope that future researchers can conduct research on how to improve student achievement with the help of technology in other subjects.